Sequencing effects of plyometric training applied before or after regular soccer training on measures of physical fitness in young players - Ramirez-Campillo, R.; Alvarez, C.; Gentil, P.; Loturco, I.; Sanchez-Sanchez, J.; Izquierdo, M.; Moran, J.; Nakamura, F. Y.; Chaabene, H.; Granacher, U. (The Journal of Strength and Conditioning Research, 2020)
To compare the effects of short-term (i.e., 7 weeks) plyometric jump training applied before (PJT-B) or after (PJT-A) soccer practice on components of physical fitness in young soccer players, a single-blind randomized controlled trial was conducted. Postpubertal boys aged 17.0 ± 0.5 years were allocated to 3 groups: PJT-B (n = 12), PJT-A (n = 14), and control (CON; n = 12). The outcome measures included tests to evaluate 20-m speed, standing long jump (SLJ), squat jump (SJ), countermovement jump (CMJ), and drop jump (DJ), 20-m multistage shuttle run endurance (MSSRT), and Illinois change-of-direction speed (ICODT). Although the CON performed soccer-specific training, the PJT-A and PJT-B groups conducted the same soccer-specific sessions but replaced ~11% of their time with plyometric training. The PJT-B group performed plyometric exercises after a warm-up program, and the PJT-A group conducted plyometric exercises ~10 minutes after the completion of soccer training. Analyses of variance were used to detect differences between groups in all variables for pretraining and posttraining tests. Main effects of time (all p < 0.01; d = 0.19-0.79) and group × time interactions (all p = 0.05; d = 0.17-0.76) were observed for all examined variables. Post hoc analyses revealed significant increases in the PJT-B group (SLJ: 9.4%, d = 1.7; CMJ: 11.2%, d = 0.75; 20-m MSSRT: 9.0%, d = 0.77) and the PJT-A group (SLJ: 3.1%, d = 0.7; CMJ: 4.9%, d = 0.27; 20-m MSSRT: 9.0%, d = 0.76). Post hoc analyses also revealed significant increases in the PJT-B group (20-m speed: -7.4%, d = 0.75; 20-cm DJ reactive strength index: 19.1%, d = 1.4; SJ: 6.3%, d = 0.44; ICODT results: -4.2%, d = 1.1). In general, our study revealed that plyometric training is effective in improving measures of physical fitness in young male soccer players when combined with regular soccer training. More specifically, larger training-induced effects on physical fitness were registered if plyometric training was conducted before soccer-specific training.